Genotipagem do vírus Epstein-Barr em amostras de raspado de borda lateral de língua de pacientes soropositivos para HIV-1 - Robaina, Tatiana Ferreira (2006)
The Epstein-Barr virus (EBV) is a member of the Herpesviridae family. It infects around 90% of the world s population. The EBV known as the etiological agent of infectious mononucleosis and oral hairy leukoplakia (OHL). The OHL is a white lesion that develops essentially at the side border of the tongue, in patients that suffer from several immunossupression, specially those affected by the human immunodeficiency virus (HIV). In these patients, the OHL is considered a diagnosed lesion of Acquired Immune Deficiency Syndrome, and has a prognostic mark for the development of this ailment. The OHL is the only epithelial manifestation known from EBV in its replicative phase, constituting an important study model for the observation of the viral action as cellular proliferation inductor, since in this phase there is an expression of practically all genes e proteins codified by its genome. Two types of EBV are recognized type-1 (EBV-1), and type-2 (EBV-2). These two genotypes can be identified because they present differences in the genes EBNA-2, 3A, 3B, and 3C; and show epidemiologic variations. The role of EBV infection, its action mechanisms in OHL pathogenesis, and the interaction of its proteins and the host are yet to be completely known. EBV genotyping studies associated to OHL are rare, and it is not established if there is prevalence of one of the EBV genotypes in this lesion in Brazilian patients. The purpose of this work was to identify the EBV prevalent genotype in 53 samples scraps lateral border of tongue in HIV-1 patients, with or without OHL, using PCR methodology based in genomic differences of the EBNA-2. Besides, an optimization of the PCR and Nested PCR genomic amplification methodology for the EBNA-2 gene, and a comparison of results in EBV genotyping with or without clinic and subclinic OHL with the epidemiologic and clinic data collected from patients were also sought. The EBV-1 genotype was identified in 41 (77,3%) samples, the EBV-2 in 22 (41,5%), and in 10 (18,9%) of these samples both genotypes were identified. There was an equivalence between the number of female (24) and male (29) samples. There was also an expressive statistic difference between the occurrence of EBV-1 in men and women, being the presence of EBV-1 higher in women. It was not found a significative statistic result that would relate one of the EBV genotypes to the development of OHL. To conclude, we found that the OHL s developing mechanism may be multifactorial and the oral epithelium in HIV soropositive patients is infected by EBV-1, EBV-2 or both EBV genotypes. The methodology developed for the research showed itself adequate and efficient in identifying the EBV genotypes with a reduction of the time of processing. In this work many important results did not present statistically expressive correlation, although they reinforce the necessity of systematic studies with a larger number of samples to investigate de EBV s genetic diversity.